(untitled) (Nigerian Journal of Technology, 2019)
This study examined the use of Prism Steel Slag (PSS) and Machine Iron Slag (MIS) as partial replacement of coarse aggregate in concrete. Coarse aggregates were partially replaced with PSS and MIS at 0%, 10%, 20%, 30%, 40% and 50% respectively. A total of 132 concrete cubes of sizes 150 mm x 150 mm x 150 mm were cast and cured in water for 7, 14, 21 and 28 days respectively. Mix ratio of 1:2:4 was adopted with w/c ratio of 0.45 and batching was done by weight. The slump result indicated that the fresh concrete becomes stiff as the percentages of PSS and MIS increases. However, the compressive strengths of concrete cubes increased as the curing ages increases. 50% PSS and 40% MIS can successfully be used as partial replacement of coarse aggregate in the production of concrete grade 20. http://dx.doi.org/10.4314/njt.v38i2.2